Translation and Validation of a State-Measure of Body Image Satisfaction: The Body Image State Scale - Bardi, Luc; Arnaud, Claire; Bagès, Céline; Langlois, Frédéric; Rousseau, Amelie (Frontiers in Psychology, 2021)
The aim of the present study is to test the validity and reliability of the French Body Image State Scale (F-BISS). The scale was translated using a back-translation technique, with discrepancies being settled through consensus. Three hundred and twelve female participants were recruited. Convergent validity was assessed using eating disorder evaluation social comparison. Exploratory and confirmatory factor analyses were also conducted. The translated BISS demonstrated good psychometric properties, with good internal consistency (α=0.83), and adequate goodness-of-fit. The translated BISS presented a unifactorial structure, with one factor explaining 56% of the variance. The exploratory factor analysis led to the removal of a single item due to insufficient factor loading (<0.45). Its convergent validity seems consistent with previous literature. Discriminant analyses showed a significant difference in F-BISS score between participants relative to eating disorder symptomatology (t = 11.65; p < 0.001). This translation could prove useful in both research and clinical settings to assess state body satisfaction in French populations.